2022
DOI: 10.1371/journal.pone.0270593
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into potential mechanisms of metabolic syndrome by integrative analysis of metabolomics and proteomics

Abstract: Metabolic syndrome (MetS) is a complex syndrome cluster of metabolic disorders, which greatly increases the risks of diabetic and cardiovascular diseases. Although it has become a significantly worldwide public health burden, its pathogenesis largely remains unknown. In this study, we first performed an integrated analysis of proteomic and metabonomic data of liver tissues of rats between MetS and control groups to reveal possible mechanisms of MetS. A total of 16 significantly perturbed pathways were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Interestingly, many of the pathways involved in the antioxidant response play crucial roles in protein synthesis, energy metabolism, and carbohydrate metabolism. This study found significant alterations in antioxidant metabolic pathways including glutathione metabolism, taurine and hypotaurine metabolism, and ascorbate and aldarate metabolism, suggesting a link between early adverse experiences and the risk of metabolic illness later in life [67][68][69][70].…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, many of the pathways involved in the antioxidant response play crucial roles in protein synthesis, energy metabolism, and carbohydrate metabolism. This study found significant alterations in antioxidant metabolic pathways including glutathione metabolism, taurine and hypotaurine metabolism, and ascorbate and aldarate metabolism, suggesting a link between early adverse experiences and the risk of metabolic illness later in life [67][68][69][70].…”
Section: Discussionmentioning
confidence: 60%
“…Krebs cycle and glycolysis are two key components inside and outside of the mitochondria, respectively, for energy production in the form of ATP in neurons and other cells [100][101][102]. In addition, the Krebs cycle is the last metabolizing hub for the metabolism of lipids, carbohydrates, and amino acids and is associated with age-related and metabolic diseases [98,101,103]. For example, in the process of aspartate conversion to asparagine, ammonia is transferred from glutamine to asparagine which converts it to glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, in a proteomic-metabolomic study of high-sugar-fat diet Wistar rats (an animal model of metabolic syndrome), 16 pathways were enriched. Three pathways were shared by metabolomics studies of serum samples from diabetic patients: 1) alanine, aspartate, and glutamate metabolism, 2) glycine, serine, and threonine metabolism, and 3) valine, leucine, and isoleucine biosynthesis [98]. Transcriptomic and metabolomic joint analysis after an immune challenge with LPS in Zebra fish, revealed enrichment of alanine, aspartate, and glutamate metabolism and aminoacyl-tRNA biosynthesis [99].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, replication of these metabolites across cohorts is lacking, and integration of additional ‘-omics’ data has been recommended to further explicate the pathophysiology of these variations in metabolite levels ( Monnerie et al, 2020 ; Comte et al, 2021 ). For example, an integrative proteomics-metabolomics analysis identified metabolic pathways that were perturbed in the setting of MetS, including serine metabolism ( Chen et al, 2022 ). Another study that combined metabolomic, proteomic, and transcriptomic data showed that mitochondrial respiratory chain dysfunction alters serine biosynthesis pathways ( Bao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%